اليقظة العقلية وعلاقتها بتقدير الذات والعوامل الخمسة الكبرى للشخصية لدى أعضاء هيئة التدريس بجامعة مصراتة (Journal of Academic Research, 2025)
AbstractThe study aimed to investigate the relationship between mindfulness, self-esteem, and the Big Five personality traits among faculty members at the University of Misurata, as well as to examine differences according to certain demographic variables such as gender and level of experience. The researcher employed a descriptive correlational design, and the sample consisted of 340 faculty members selected through simple random sampling. The instruments used were the Mindfulness Scale (Bera et al., 2006), the Self-Esteem Scale (Mohamed, 2018), and the Big Five Personality Inventory (Costa & McCrae, 1992).The findings revealed a positive and statistically significant correlation between mindfulness, self-esteem, and the Big Five personality traits. Significant gender differences were found in mindfulness and self-esteem in favor of males, as well as in the Big Five personality traits, except for neuroticism and agreeableness. No significant differences were observed between less and more experienced faculty members in mindfulness and the Big Five traits; however, significant differences emerged in self-esteem, favoring those with higher experience                                                                                .The results were interpreted in light of theoretical frameworks and previous studies, and the researcher proposed a set of recommendations and future research directions, emphasizing the importance of fostering mindfulness and self-esteem among university faculty                                       Keywords: Mindfulness – Self-esteem – Big Five Personality Traits